JOHN WANSBROUGH: STUDI ATAS TRADISI DAN INSTRUMEN TAFSIR ALQUR’AN KLASIK - Syamsul Wathani (UIN Raden Mas Said Surakarta, 2018)
This study discusses John Wansbrough's thoughts on Alquran interpretations, which emphasize the two important points as its focus of the study; interpretation paradigm and positioning of the scriptural interpretations. Based on the content analysis method as its analytical tool from the various works, both those directly and indirectly related to Wansbrough's thoughts, the results of this study showed that there are two lines of understanding of interpretations: first, the interpretation is seen as an act of interpreting the scriptures, in which in its process there are rules, work procedures, and thinking patterns that continue to grow. The existence of an exegete becomes a parameter of the interpretations produced. Interpretation and exegete are two things that are interrelated each other. Second, interpretation has an exegetical device inherent in the interpreter, which then produce the exegetical types of explicative elements or procedural devices used by an interpreter.